Up-scale study on ultrasonically assisted of biodiesel production from waste cooking oil (WCO) - Florina, Geduin (2008)
Up-scale for the production of biodiesel from waste cooking oil (WCO) and Refined-Bleached-Deodorized (RBD) under ultrasonic condition was studied. The effects of sodium hydroxide as a catalyst and time on the biodiesel conversion were investigated. Experiments have been performed to determine the optimum condition for this alkali-catalyzed transesterification process where the temperature is fixing at 40ºC and the stirring rpm are 1000 rpm. The results showed that transesterification process under ultrasonic condition was proved to be time and energy saving. Gas Chromatography (GC) is used to study the formation of methyl ester of waste cooking oil and combustion test to study the combustion characteristic of biodiesel. The optimum experimental condition for catalyst concentration is 1 wt% sodium hydroxide (NaOH) and the reaction time is 40 minutes for WCO while 0.75 wt % sodium hydroxide (NaOH) and the reaction time is 30 minutes for RBD. The level of carbon dioxide (CO2) and carbon monoxide (CO) in biodiesel from WCO are low compare to the RBD and diesel fuel.